First Images of a Three-Layer Compton Telescope Prototype for Treatment Monitoring in Hadron Therapy - Llosá, Gabriela; Trovato, Marco; Barrio, John; Etxebeste, Ane; Muñoz, Enrique; Lacasta, Carlos; Oliver, Josep F.; Rafecas, Magdalena; Solaz, Carles; Solevi, Paola (Frontiers in Oncology, 2016)
A Compton telescope for dose monitoring in hadron therapy is under development at IFIC. The system consists of three layers of LaBr3 crystals coupled to silicon photomultiplier arrays. 22Na sources have been successfully imaged reconstructing the data with an ML-EM code. Calibration and temperature stabilization are necessary for the prototype operation at low coincidence rates. A spatial resolution of 7.8 mm FWHM has been obtained in the first imaging tests.